PEMANFAATAN BAMBU DAN PEWARNA JARENANG SEBAGAI BAHAN PELENGKAP KERAJINAN ROTAN : N u w a - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT Jarenang colouration coming from latex of Jarenang fruit (Daemonorops sp) species that grow well at the low land forest. Generally jerenang colouration has used to colouring wood, stone, vernis, ceramics, paper and paint etc. This substance also can to be used as medicine of dysentery, blood solidification, leather tanner and cosmetics material. The experiment was conducted at the social community group named Silip Rawi that be located at the Bukit Rawi Village, Kahayan Hilir District, Central Kalimantan Province. Silip Rawi group has guided by Science and Technology for Community Program (IbM). This experiment applied jerenang colouration to colouring bamboo as complement material of rattan handicraft. Some stages of this experiment as follow: First, cleaving bamboo and make s.t. thin. Second, colouring the bamboo using colour of red, black, blue ect. Then colored bamboo was dehydrated using sunlight. Finaly, colored bamboo as insertion insert to rattan handicraft to improve quality of them. Colored bamboo create the motif of line, curve, numeral, figure, scribal of personal or group name, village nama, city name etc. at the rattan handicraft to raise the sale price. Keynotes: Bamboo, colouring, jarenang, rattan handicraft.